Partial replacement of wheat flour (triticum durum) with sweet potato flour (ipomoea batata) and maca (lepidium meyenii) in pastry product: alfajores - Amara K. Haro-Quiñones (2025)
With the purpose of improving the quality and nutritional value of baking products, the idea of designing alfajores was proposed by partially replacing wheat flour with sweet potato and maca flour. This approach is aimed at offering products with high levels of nutrients present in sweet potato and maca. The main objective of this study is to evaluate the acceptance of alfajores made with these flours, using raw materials grown and produced in Peru. The research was carried out in the Ancash region, specifically at the facilities of the National University of Santa. To obtain the sweet potato and maca flour, the same procedure was followed: 15 kg of raw material was used, which was subjected to a disinfection process and then dried for 48 hours at 55 °C. As a result, 2.7 kg of sweet potato flour and 3.5 kg of maca flour were obtained. The formulations used in the preparation of alfajores were 75 % wheat flour, 22.5 % sweet potato flour and 2.5 % maca flour. The estimated yield was 240 units of alfajores, based on 6 kg of total flour. The sensory analysis was evaluated regarding color, flavor, texture and purchase intensity, where it is highlighted that in all evaluations a high acceptability of the planning Alfajores.